Analysis of the Effect of Tuyere Angle on Velocity and Temperature Distribution in a Blast Furnace Using Computational Fluid Dynamics Method - Bahiy, Oktavian Khayyan; Abdul Shaleh, Mansyur (Journal of Metallurgical Engineering and Processing Technology, 2025)
This study aims to explore the impact of tuyere angle variation on velocity and temperature distribution in a blast furnace using Computational Fluid Dynamics (CFD) methods. The tuyere angles analyzed in this research include 4°, 6°, 8°, and 10°. Understanding the resulting velocity and temperature distributions from these variations is crucial in metallurgical processes, as it directly affects thermal efficiency and the quality of the end product. Simulation results revealed that increasing the tuyere angle from 4° to 8° led to more stable and uniform airflow patterns, as well as optimal heat distribution. However, when the tuyere angle was further increased to 10°, there was a noticeable instability in airflow and temperature distribution, which resulted in a decrease in process efficiency. This indicates a direct correlation between the increase in tuyere angle and flow stability up to the optimal point at 8°, beyond which performance declines. The study concludes that an 8° tuyere angle is the most ideal for use in blast furnaces, as it provides the most efficient heat distribution and airflow.